The political child: An essay about life, philosophy, the political and science - Reinertsen, Anne Beate (Reconceptualizing Educational Research Methodology, 2024)
This essay is an attempt to write un unruly force field in sustained expansions about the political child, life, philosophy, policies, and science. Unruly as in messy and stammering but open. Unruly about the political child as a force and carrier of immanence, unencumbered, and as an expression of a future. It implies a view of the child born with inalienable rights as a political subject and force of material and social transformation, and temporalities of writing being transformational techniques. Writing ultimately treated as an ecological practice and method that facilitates the production of collective subjectivities. Thinking the child, life, science, and the world politically means thinking with Chantal Mouffe’s (2015) concept agonism in combination with writing as continual Deleuze and Guattarian (2004a) becomings, active in life itself. There are thin walls between realisms, dreams and fabulations, and this essay is an attempt to strike a blow for freer, humorous, more philosophical, and political mindsets in our pedagogical sciences and imaginations. Therefore, there are also unruly words and sometimes not yet present.